PENGAJARAN IDEAL DALAM PENDIDIKAN ISLAM - Nuruzzahri Nuruzzahri (SCAD Independent, 2014)
A teacher or a lecturer does not only act as a tutor in the art of teaching but also act as an educator who provides guidance for the students. An educator must have a level of quality standard sets upon his or her teachings which incorporates values such as responsibility, authoritative as well as high discipline. Having all these values will be beneficial in the learning process which will maximize effort taken to fruition by observing and practicing the concept offered in Islam. Besides that, it is an educator’s role to instill and internalize Islamic values among the students they teach in order to prepare them in the development towards Islamic values dynamically and flexible within the boundaries of Islamic teachings based on Allah SWT’s revelation to his servants.